Larysa Djavdetivna (Yevgenivna) Gonchar - “Orthopaedics, Traumatology; Prosthetics”, Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is devoted to a talented teacher who was admired by the cadets; to a thoughtful doctor who seeks to determine the cause of the disease; to the talented scientist Goncharova L. J.